PENINGKATAN PENGETAHUAN DAN KETERAMPILAN DASAR DALAM PELAYANAN KEFARMASIAN DI APOTEK BAGI LULUSAN SMK FARMASI NOL TAHUN DI KOTA PALEMBANG - Dewi Astuti, Ratnaningsih; Taswin, Muhamad (Jurnal Pengabdian kepada Masyarakat (ABDIKEMAS), 2020)
One level of education that contributes to the workforce is vocational high school (SMK). Pharmacy Vocational School graduates do not have adequate skills and abilities in administrative management in pharmacies so that results are still not good. The impact is that graduates of Pharmacy Vocational Schools are generally not ready to work in the world of work, they need an internship first to get used to working in a pharmacy. The Department of Pharmacy, Poltekkes Palembang, as a partner institution that APMFI has always asked for as examiners at the UPK of Pharmacy Vocational Schools in South Sumatra, has improved the basic knowledge and skills of zero-year Pharmacy Vocational School graduates in the city of Palembang in pharmaceutical services at pharmacies so that they become more ready to use, through training activities in the form of theoretical presentation accompanied by individual practice and group service simulations. The pretest results of the training participants with an average point of 7.91 showed that only about 50% of the material they knew and from the posttest results obtained an average of 10.67, which is about 70% of the material. The lowest score from 4 increased to 7 and the highest score increased from 12 (1 person) to 14 (3 person). From the statistical test of paired t-test (p<0.05) it was found that the results of the pretest-posttest showed a significant change. The conclusion of community service from the Department of Pharmacy with the theme of Increasing Basic Knowledge and Skills in Pharmaceutical Services at Pharmacies for Graduates of the Zero Year Pharmacy Vocational School in Palembang City shows positive and beneficial results for its targets. In addition, this activity has also been able to introduce the Department of Pharmacy to Pharmacy Vocational School graduates so that it is expected to increase the interest of Sipenmaru Poltekkes Palembang participants in 2016 in general and in particular the Department of Pharmacy.